NEW PEDAGOGICAL TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Ishonkulov Sherzod Usmonovich (Western European Studies, 2024)
The landscape of foreign language learning is undergoing a significant transformation due to the emergence of new pedagogical technologies. This article explores the potential of these technologies to enhance the learning experience and improve student outcomes. We discuss various innovative tools and approaches, including computer-assisted language learning (CALL), mobile applications, gamification, and online collaborative learning platforms. The article analyzes the benefits and limitations of these technologies, emphasizing their ability to promote personalization, interactivity, and engagement in language acquisition. We conclude by highlighting the importance of integrating these tools effectively within a well-designed pedagogical framework to maximize their impact on foreign language learning.
Keywords: Foreign language learning; Pedagogical technologies; CALL; Personalization